Identifikasi Potensi Bahaya Dalam Aktivitas Pemeliharaan Listrik Dengan Metode HIRARC & FTA Pada PLN ULP Ajibarang - Nurlita, Laela; Ferida Yuamita (KAMPUS AKADEMIK PUBLISING, 2026)
Electrical network maintenance activities pose a significant level of occupational safety and health (OHS) risk, particularly those involving live networks and working at heights. These conditions contribute to the continued occurrence of near-miss incidents during electrical maintenance at PLN ULP Ajibarang. This study aims to examine near-miss incidents, identify potential hazards, evaluate the OHS risk level, and develop risk control recommendations for electrical network maintenance activities. The FTA method was employed to trace the root causes of near-misses, whereas the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) approach was applied to assess the risk level and determine appropriate control measures. The analysis results indicate that near-miss incidents are influenced by a combination of unsafe conditions and unsafe acts stemming from human factors, equipment, work methods, and the work environment. Based on the risk assessment using HIRARC, nine potential hazards were identified, classified as 4 high, 14 medium, and 11 low. Risk control efforts focused on extreme hazards by applying administrative control measures and utilizing Personal Protective Equipment (PPE).